CARE: Diabetes Screening With The Utilization of Family Medicinal Plants (TOGA) - Riza Tsalatsatul Mufida; Sherly Anggraini Wiyono; Vhiendy Putri Destiananda; Saiva Alifia; Vestin Aulia Firdaus; Citra Dewi Anggraini; Lutfhia Putri Andarista; Reandi Ayana Messi; Muhaimin; Kania Sukma Lembar Diningrum; Risma Dwi Utami; Valeria Oktaviani Kasna; Anggi Nur Prasetio; Susanti Inya Mete; Riza Niko Alviyansyah (Journal of Community Engagement in Health, 2026)
Health is a fundamental pillar of community life, closely linked to quality of life and productivity. One promising preventive effort closely linked is the utilization of Family Medicinal Plants (TOGA), which are herbal plants cultivated in home gardens and known for their medicinal properties. This community service program aims to enhance the knowledge and skills of residents in Mangunrejo Village, particularly in Dusun Munengan, in processing TOGA into safe, practical, and economically valuable health beverage products. The method used to employ in this program involves a participatory approach through education, training, and community mentoring. The plants focused on are clove, sappan wood, and cinnamon, which contain active compounds such as eugenol, brazilin, and cinnamaldehyde—proven to have health benefits such as antioxidant, antidiabetic, and anti-inflammatory effects. Residents were actively involved in every step, from plant identification and processing to the development of final products such as herbal tea bags and ready-to-drink spiced beverages.